Pembuatan lem sintetik dan aplikasinya pada alas kaki - Yuniari, Arum; Herminiwati, Herminiwati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2008)
Footwear can be categorized as one of labour intensive and very superior export commodities, consequently the product quality must be maintained and be continually improved. The quality parameter of footwear is determined by the bonding strength between the uppers and the soles, it means that it depends on the adhesive applied. Soling system is widely applied in small and medium industries are cemented system used synthetic adhesive. Now, the adhesive was applied in the manufacturing of foot wear supported by binding of the soles and the uppers is easy to peel off because of the poor bonding strength. The aim of the research was to investigate a suitable synthetic adhesive formula to used in footwear manufacturing. In preparing of the adhesive formula, the effect of phenolic resin addition as tackifier were varies i.e 35, 45 and 55 phr using chloroprene rubber as raw material were observed. Synthetic adhesive compound was produce by two roll mill after that compound were dissolved in toluene with ratio 1 : 3. The prepared adhesive then was applied to manufacture footwear using cool press system. The soles used in the experiment were made of rubber and plastic material whereas the uppers made of either leather or artificial leather. The test result and data analysis showed that adhesive performed for the highest bonding strength as much as 1000 g/cm and decrease to lowest bonding strength after soaking in to water for 500 seconds one percent was obtained by the following formula that were : chloroprene rubber 100 phr, butylated hydroxyl toluene 2 phr, magnesium oxide 4 phr, zinc oxide 5 phr and phenolic resin 45 phr. The prepared formula performed a better bonding strength when it was compared with chloroperene rubber adhesive in market. The application of this prepared formula in making ladies shoes performed good bonding strength and accordance with the requierments of SNI 12-2942-1992 about Leather Pantopel Style Cemented System Ladies Shoes. Key words: synthetic adhesive, chloroprene rubber, footwear. ABSTRAK Alas kaki merupakan salah satu komoditi andalan ekspor yang bersifat padat karya dan banyak menyerap tenaga kerja, sehingga kualitasnya harus selalu dijaga dan terus ditingkatkan. Kualitas alas kaki salah satunya ditentukan dari kekuatan rekat bagian atas sepatu dengan sol yang dipengaruhi oleh lemnya. Sistem pengesolan yang banyak digunakan di industri kecil dan menengah adalah system lem, menggunakan lem sintetik. Saat ini lem yang digunakan dalam pembuatan alas kaki mudah mengelupas apabila sering terkena air karena kuat rekatnya masih rendah. Tujuan penelitian adalah mendapatkan formula lem sintetik yang tepat untuk digunakan pada pembuatan alas kaki. Dalam pembuatan lem ini dipelajari pengaruh penggunaan phenolik resin sebagai tackifier berturut-turut sebesar 35 : 45 dan 55 phr dengan bahan baku chloroprene rubber. Pembuatan kompon lem dilakukan dengan mesin two roll mill dan selanjutnya lem dilarutkan dalam toluene dengan perbandingan 1 bagian kompon dan 3 bagian tuluen. Selanjutnya lem yang dibuat digunakan untuk pembuatan alas kaki dengan system lem pres dingin. Sol yang digunakan adalah sol karet dan plastik dengan bahan atasan dari kulit maupun kulit imitasi. Hasil uji dan analisa data menunjukkan bahwa lem yang mempunyai kuat rekat optimum sebesar 1000 g/cm dan penurunan kuat rekat yang terendah setelah perendaman dalam air selama 500 detik sebesar 1 % adalah lem dengan formula : chlroroprene rubber 100 phr, butylated hydroxyl toluene 2 phr, magnesium oxide 4 phr, zinc oxide 5 phr dan phenolic resin 45 phr. Formula tersebut mempunyai kuat rekat lebih tinggi disbanding lem chloroprene rubber dari pasaran. Aplikasinya untuk sepatu wanita memberikan nilai kuat rekat baik dan memenuhi SNI 12-2942-1992 sepatu wanita dari kulit model pantopel sistem lem. Kata Kunci: lem sintetik, chloroprene rubber, alas kaki.